Interaction study of cancer cells and fibroblasts on a spatially confined oxygen gradient microfluidic chip to investigate the tumor microenvironment. Issue 22 (12th October 2018) - Sun, Wei; Chen, Yuqing; Wang, Yuerong; Luo, Pei; Zhang, Min; Zhang, Hongyang; Hu, Ping
Abstract : This paper reports a single-layered microfluidic device for studying the interaction of cancer cells and fibroblasts in an oxygen gradient. Abstract : This paper reports a single-layered microfluidic device for studying the interaction of cancer cells and fibroblasts in an oxygen gradient. This gradient can be established from 1.9% to 18.8% using a spatially confined oxygen scavenging chemical reaction. Due to the spatial design of the chip, only cancer cells can sustain low oxygen conditions when co-cultured with fibroblasts in the adjacent channels, simulating the cell–cell interactions of the hypoxic cancer cells and the surrounding fibroblasts in tumor microenvironment in vivo . Moreover, a cell migration assay is performed on the chip for studying the tumor invasion ability. The results show that the migration speed of B16 cells is increased by hypoxia and the co-culture with L929 cells. In addition, we use ELISA to quantify the migration-related cytokines transforming growth factor-β1 (TGF-β1) in the microfluidic system. Our results confirm interaction between cancer cells and fibroblasts. This microfluidic device provides new insight for the investigation of tumor microenvironment and cell interactions.